A double-blind, randomized study comparing pure chromated glycerin with chromated glycerin with 1% lidocaine and epinephrine for sclerotherapy of telangiectasias and reticular veins - Kern, P.; Ramelet, Anne-Sylvie; Wutschert, R.; Mazzolai, L. (2011)
Background: Chromated glycerin (CG) is an effective, although painful, sclerosing agent for telangiectasias and reticular leg veins treatment. OBJECTIVE To determine pain level and relative efficacy of pure or one-third lidocaine-epinephrine 1% mixed chromated glycerin in a prospective randomized double-blind trial. METHOD Patients presenting with telangiectasias and reticular leg veins on the lateral aspect of the thigh (C 1A or SE PA SP N1) were randomized to receive pure CG or CG mixed with one-third lidocaine-epinephrine 1% (CGX) treatment. Lower limb photographs were taken before and after treatment and analyzed by blinded expert reviewers for efficacy assessment (visual vein disappearance). Patients' pain and satisfaction were assessed using visual analogue scales. Results: Data from 102 of 110 randomized patients could be evaluated. Patient pain scores were significantly higher when pure CG was used than with CGX (p<.001). Patient satisfaction with treatment outcome was similar in the two groups. Objective visual assessment of vessel disappearance revealed no significant difference between the two agents (p=.07). CONCLUSION Addition of lidocaine-epinephrine 1% to CG, in a ratio of one-third, significantly reduces sclerotherapy pain without affecting efficacy when treating telangiectasias and reticular leg veins. The authors have indicated no significant interest with commercial supporters. © 2011 by the American Society for Dermatologic Surgery, Inc.